The Hindu Kush slab break-off as revealed by deep structure and crustal deformation - Sofia-Katerina Kufner (Nature Portfolio, 2021)
Here, the authors document active slab break-off and the crustal response during continental collision under the Hindu Kush, a rarely observed process since it happens over geologically short time spans.